CONSUMER MARKET SEGMENTATION IN PT. VERONICCA PUTRI MEUTUAH TOUR AND TRAVEL PEKANBARU - Aisyah Rahman; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine Consumer Segmentation at PT. Veronicca Putri Meutuah Tour and Travel Pekanbaru. The population in this study were consumers who bought flight tickets in the 2016-2019 purchase period, totaling 14,318 tickets sold. The number of samples used was 100 people using the Slovin formula. Data collection was carried out using qualitative descriptive methods using survey sheets (questionnaires), observations, interviews and documentation. The results of this study indicate segmentation is divided into 4 aspects according to Kotler 1992 in Sunyoto 2012: 57-62 namely geographic segmentation, demographic segmentation, psychographic segmentation and behavioristic segmentation. With the demographic segmentation variables, behavior and geography are very significant in the grouping of consumers in PT. Veronicca Putri Meutuah. And the results of the survey sheet have been tested using a measuring instrument that is the validity test and reliability test with the results of the questions asked to consumers have proven to be valid and reliable. Keywords: Consumer market Segmentation, Geographic market Segmentation, Demographic market Segmentation, Psychographic market Segmentation and Behavioristic market Segmentation (Behavior)